Effect of CaCl2, Al(OH)3 and NH4H2PO4 and their dosages on the explosion intensity of pulverized coal. Issue 3 (14th September 2022) - Ren, Xiaofeng; Zhang, Jiangshi; Fang, Lei; Hu, Zimin; Tong, Linquan
ABSTRACT: In this paper, the TGA-DSC curve of coal powder explosion inhibitors was analyzed. At the same time, the influence of the explosion inhibitor type and mass fraction on the five explosion intensity parameters of pulverized coal Pex, (dp/dt)ex, Kst, t1, and t2 was explored. The results show that CaCl2 and NH4 H2 PO4 go through three main stages: dehydration stage, decomposition stage and crystal transformation stage after high-temperature heating. Calcium chloride absorbs heat through the process of water volatilization and crystal transformation to prevent the combustion of pulverized coal. Meanwhile, NH4 H2 PO4 absorbs heat through decomposition, evaporation and sublimation reactions to prevent the combustion of pulverized coal. For these two explosion inhibitors, the explosion intensity of pulverized coal decreases with the increase of mass fraction. The increase of Al(OH)3 mass fraction basically does not enhance its explosion suppression effect. After adding NH4 H2 PO4, the maximum decrease of Pex was 32.08%, which was 11.89% and 16.99% higher compared to the addition of CaCl2 and Al(OH)3, respectively. The maximum decrease of (dp/dt)ex was 98.47%, which was 29.45% and 33.38% higher compared to the addition of CaCl2 and Al(OH)3, respectively. Therefore, the order of explosion suppression performance was determined as: NH4 H2 PO4 > CaCl2 > Al(OH)3.